2011
DOI: 10.1103/physreva.84.013609
|View full text |Cite
|
Sign up to set email alerts
|

πjunction and spontaneous current state in a superfluid Fermi gas

Abstract: We discuss an idea to realize a spontaneous current in a superfluid Fermi gas. When a polarized Fermi superfluid (N ↑ > N ↓ , where N σ is the number of atoms in the hyperfine state described by pseudospin σ =↑, ↓.) is loaded onto a ring-shaped trap with a weak potential barrier, some of excess atoms (∆N = N ↑ −N ↓ ) are localized around the barrier. As shown in our previous paper [T.Kashimura, S. Tsuchiya, and Y. Ohashi, Phys. Rev. A 82, 033617 (2010)], this polarized potential barrier works as a π-junction i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It is expected that another novel FFLO state is stabilized by the rotation. A related work has been given by Kashimura et al They showed that a spontaneous current appears in a toroidal trap with a potential barrier [26], but they didn't investigate the effect of rotation. In this paper, we investigate the FFLO phases induced by the rotation.…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that another novel FFLO state is stabilized by the rotation. A related work has been given by Kashimura et al They showed that a spontaneous current appears in a toroidal trap with a potential barrier [26], but they didn't investigate the effect of rotation. In this paper, we investigate the FFLO phases induced by the rotation.…”
Section: Introductionmentioning
confidence: 99%
“…Such currents have recently been observed in superconducting networks [6]. Realization of this idea in superfluid fermionic cold gases in a ring-shaped trap has been proposed [7].…”
Section: Introductionmentioning
confidence: 92%
“…This presents an exciting opportunity to study the Kibble-Zurek mechanism with fermions [33] in the annular geometry originally proposed by Zurek [34]. These experiments were conducted with an unpolarized Fermi gas in a ring, but a weakly polarized gas could enable the creation of matter-wave circuits with π-Josephson junctions [35] and provide a new opportunity to search for exotic spin-polarized superfluid phases [36,37]. Finally, the tight transverse confinement achieved in these experiments is not far from the quasi-1D limit, and it may be feasible to create 1D quantum rings [38] of fermions with tunable interactions, where non-Fermi-liquid behavior is expected and parity effects can be significant [39].…”
mentioning
confidence: 99%